PENYUSUNAN MODUL PEMBIASAAN/INTEGRASI KETERAMPILAN PERDAMAIAN DAN RESOLUSI KONFLIK UNTUK SEKOLAH ERENOS, TANGERANG SELATAN - Elyzabeth Bonethe Nasution; Edwin M. B. Tambunan (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
As the follow up of our community service “Workshop of Peace and Conflict Resolution Skill for Sekolah Erenos” that was conducted in 2018-2019, Youth & Peace Project of Department of International Relations together with Sekolah Erenos acknowledged the necessity of integrating peace education sustainably into learning process at school. This is crucial as character building is not an instant process; it requires discipline, commitment, and a blueprint. For this, our team with Sekolah Erenos agreed to continue our community service in form of module writing. This community service aims to create an integration module that will be used in daily learning process. Inside there will be an integration of the school’s vision and mission with peace and conflict resolution skills through intra-curricular activities from various subjects, so the students will be able to have an internalization. The module writing process will entail series of Focus Group Discussion (FGD) and workshop that focus on: (1) Sekolah Erenos’ vision and mission, (2) Characters and Values, (3) Integration Strategy, (4) Module Presentation, (5) Activities and Evaluation, (6) Module Organizational, Content, and Writer. The process will gradually incorporate the results of FGDs and workshop into a module that will entirely be the school’s ownership.